2019
DOI: 10.1002/cre2.180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of changes in the upper airway after Twin Block treatment in patients with Class II malocclusion

Abstract: The purpose of this prospective case control study is to describe in growing patients with mandibular hypoplasia, treatment outcomes following functional therapy in terms of volumetric changes in nasopharynx and oropharynx, that is, upper and lower pharynx. We recruited 60 study participants aged between 8 and 12 years having mandibular Class II malocclusion and a reduced upper airway (UA) size, as determined by McNamara cephalometric analyses. Forty patients received Twin Block treatment, whereas the remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…Additionally, Zhang et al [ 21 ] and Shete and Bhad [ 22 ] reported that TB appliance may improve the obstructive sleep apnea (OSA) symptoms in patients with mandibular retrognathia. Generally, the pharyngeal airway dimension changes following functional therapy were examined through two-dimensional (2D) lateral cephalograms [ 23 25 ] or 2D cephalometry extracted from cone beam computed tomography (CBCT) [ 26 , 27 ]. However, because of its 2D nature and inability to provide volumetric data, the value of lateral cephalograms is limited in the studies concerning the airway.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Zhang et al [ 21 ] and Shete and Bhad [ 22 ] reported that TB appliance may improve the obstructive sleep apnea (OSA) symptoms in patients with mandibular retrognathia. Generally, the pharyngeal airway dimension changes following functional therapy were examined through two-dimensional (2D) lateral cephalograms [ 23 25 ] or 2D cephalometry extracted from cone beam computed tomography (CBCT) [ 26 , 27 ]. However, because of its 2D nature and inability to provide volumetric data, the value of lateral cephalograms is limited in the studies concerning the airway.…”
Section: Introductionmentioning
confidence: 99%
“…All 20 included studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] were nonrandomized (Table 1), with only 4 studies (20%) being prospective. All studies were conducted within a university setting (one jointly with a hospital) in 9 different countries (Brazil, Egypt, India, Italy, Pakistan, Spain, Sweden, Turkey, and the United States of America).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…As functional appliances, the Twin-Block appliances with maxillary expander are used at an early stage to wide the maxillary arch, release the retracted mandible, balance the muscles and beautify the facial pro le to a certain extent [5] . With the improved anteroposterior relation between maxilla and mandible, the tongue and hyoid bone following move forward, which may increase the volume of the UA theoretically [4,6] and be gradually concerned by orthodontists.…”
Section: Introductionmentioning
confidence: 99%